Building the plane as you fly it: young diasporan engagement in Ethiopian development - Abebe, A (2016)
This thesis explores the relationship between identity, social interaction, and social practice, through a case study of young diasporans of Ethiopian origin (YDEOs) from North America and their engagements in Ethiopian development initiatives. Specifically, I examine the ways in which people of Ethiopian descent born and/or raised in Canada and the U.S. construct a diasporic identity and engage with Ethiopian development initiatives through a mutually constitutive process. My methods were qualitative and involved conducting semi-structured in-depth interviews with 55 YDEOs and attending 8 community events in Toronto, Washington, D.C., and Addis Ababa. All of the YDEOs I interviewed had actively engaged in initiatives (based in North America or Ethiopia) intended to contribute towards the social, political, and/or economic development of Ethiopia. Their initiatives included fundraising events, establishing local NGOs, volunteer missions, and taking professional positions within the Ethiopian development sector, among others. Utilising an interactionist theoretical framework, I unpack YDEO motivations for engaging in Ethiopian development, the nature of the development activities themselves, and the ways in which these experiences have shaped YDEO relationships, identities, and trajectories in life so far. Engaging in Ethiopian development was rarely expressed as an extension of a pre-existing sense of Ethiopian patriotism; rather, YDEOs used these practices to explore, test, or build a sense of connection to their country of origin. Further, the development framework made it possible for them to forge a relationship that also resonated with their other social identities, and could even be leveraged to further other personal and professional goals. YDEO engagements in Ethiopian development were not simply interventions; they were fundamentally social processes defined by social interactions. In the process of organising fundraising events, volunteering at orphanages, and working on project reports, YDEOs were also building personal connections, gaining social capital, and redefining attitudes towards their families, communities, development, and Ethiopia itself. This thesis contributes an in-depth and critical analysis of the diaspora/development nexus – a nexus that emerges as a contested space, where people act and are acted upon, where identities are reified and transformed, and where institutions and social structures are both strengthened and challenged. The insights from migrant descendant experiences, such as YDEOs, highlights the ways in which diasporic identities take shape and are imbued with meaning through social practice, and how these practices are connected to broader human psychosocial needs, aspirations, and behaviours.